Building C libraries : windows, menus & user interfaces - Dorfman, Len. (Blue Ridge Summit, PA : TAB Windcrest Books, 1990)
Practical advice for minimizing repetitious programming tasks and producing fast, tight object modules with Microsoft 5.1 Turbo, Quick and Watcom compilers. The author provides plug-in code control, keyboard input, Lotus and grid-style windows and scroll bars.
Introduction to Libraries. Introduction to Windows. Writing to the Screen. Building the Library. TSR Pop-up Windows. Putting it all Together.
Includes index.
Keywords: C (COMPUTER PROGRAM LANGUAGE)